International Capital Flows and Development : Financial Openness Matters - Ricci, Luca (IMF Working Papers; Working Paper ;, 2010)
Does capital flow from rich to poor countries? We revisit the Lucas paradox and explore the role of capital account restrictions in shaping capital flows at various stages of economic development. We find that, when accounting for the degree of capital account openness, the prediction of the neoclassical theory is confirmed: less developed countries tend to experience net capital inflows and more developed countries tend to experience net capital outflows, conditional of various countries' characteristics. The findings are driven by foreign direct investment, portfolio equity investment, and to some extent by loans to the private sector.